GRP-164 Rivaroxaban Versus Enoxaparin: Comparison of Outpatient Treatment Adherence in Clinical Practise. (12th March 2013) - Morgado, M; Ribeiro, M; Oliveira, R; Martinez, J; Morgado, S
Abstract : Background: Rivaroxaban (Riv) is a selective, direct Factor Xa inhibitor indicated in the prevention of venous thromboembolism in adult patients undergoing elective hip or knee replacement surgery (HKRS). [1] It was introduced into the pharmacotherapeutic formulary of the Hospital Centre of Cova da Beira (CHCB) in February 2011. It is administered orally, which is a potential advantage in terms of compliance when compared to enoxaparin (Eno). Purpose: To compare adherence to Eno versus Riv in adult patients undergoing elective HKRS. The occurrence of adverse drug reactions (ADRs) was also compared between the groups. Materials and Methods: Cross-sectional study of outpatient compliance to Eno or Riv, in patients undergoing KHRS in CHCB, from February/2011 to April/2012. Medicines adherence was evaluated using a validated questionnaire and the occurrence of ADRs was evaluated in a structured interview. Results: The study included a total of 60 patients, who underwent elective knee (29 patients) or hip (31 patients) surgery; 41 patients were treated with Eno (17 knee + 24 hip) and 19 with Riv (12 knee + 7 hip). In all, 91.7% patients were considered adherent to the treatment, but a significant difference (P = 1) was not observed between patients anticoagulated with Eno (92.7% adherent) or Riv (89.5% adherent). Similarly, there was no significant difference (P = 0.35) in treatment adherence between patients undergoing knee or hip surgery. However, there was a significantly higher occurrence of ADRs (P = 0.001) in patients treated with Eno (39.0%; hematoma at the site of injection) when compared to patients treated with Riv (no ADRs were attributable to this drug). Conclusions: Although a significant difference in adherence to subcutaneous Eno vs oral Riv was not observed, which may be potentially attributed to the short-term anticoagulation treatment (2 to 5 weeks), the occurrence of ADRs was significantly lower in patients treated with the oral anticoagulant. This difference in drug-related adverse events differs from other studies that detected similar adverse-event profiles.[2] From a methodological point of view, this is a small cross-sectional study and our results must be considered exploratory in nature. References: Abrams PJ, Emerson CR. Rivaroxaban: A novel, oral, direct factor Xa inhibitor. Pharmacotherapy . 2009;29(2):167–181. Lassen MR, Ageno W, Borris LC, Lieberman JR, Rosencher N, Bandel TJ, et al, Rivaroxaban versus enoxaparin for thromboprophylaxis after total knee arthroplasty. N Engl J Med 2008;358:2776–86. No conflict of interest.